2019
DOI: 10.1101/622183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circadian regulation of microRNA-target chimeras in Drosophila

Abstract: 41MicroRNA is critical coordinator to circadian regulation by silencing gene 42 expression. Although many circadian related miRNAs and some of its target are 43 known, the global functional miRNA-mRNA interaction networks remain poorly 44 understand which is hindered by imperfect base-pairing between miRNA and target 45 mRNA. In this study, we used CLEAR (Covalent Ligation of Endogenous 46Argonaute-bound RNAs) -CLIP (Cross-Linking and Immuno-Precipitation) to explore 47 the regulatory functions of miRNAs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…MiR-133a and miR-133b are involved in muscle proliferation, repair and regeneration, and both these miRNAs are up-regulated in ALS patients [171][172][173]. It has been reported that miR-133, which is highly conserved, contributes to core circadian gene expression based on the significant differences observed between a clock mutant and wild type fly [174]. In addition, miR-142 is up-regulated in the spinal cord of sporadic ALS patients [173].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…MiR-133a and miR-133b are involved in muscle proliferation, repair and regeneration, and both these miRNAs are up-regulated in ALS patients [171][172][173]. It has been reported that miR-133, which is highly conserved, contributes to core circadian gene expression based on the significant differences observed between a clock mutant and wild type fly [174]. In addition, miR-142 is up-regulated in the spinal cord of sporadic ALS patients [173].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%